Improving Students' Collaboration Ability and Scientific Literacy through the Group Investigation Type Cooperative Learning Model - Prayoga, Kadek Sonia; Gading, I Ketut (Universitas Pendidikan Ganesha, 2023)
Many factors influence scientific literacy, including students' lack of activeness and interest in reading in the learning process. Based on the observations, it was found that students' collaboration abilities still needed to be higher, with a percentage of 60% not understanding collaboration. This is because students are less active in communicating and interacting, and the learning model applied by teachers needs to be more creative and innovative. This research examines the effect of the Group Investigation (GI) type cooperative learning model on the collaboration abilities and scientific literacy of fifth-grade elementary school students. The type of research carried out was experimental research, with a nonequivalent pre-test and post-test control group design. The population of this study was 133 students. The sample in this study involved 19 students in the experimental class and 18 students in the control class. Collaboration ability data was collected using questionnaire instruments and test instruments in the form of objective questions for scientific literacy. Next, the data was analyzed using descriptive and inferential statistical techniques (t-test and Manova). Based on the t-test analysis, it was found that simultaneously, the GI-type cooperative learning model influenced students' collaboration abilities and scientific literacy. Based on descriptive analysis, the average score of the experimental group was more significant than the average score of the control group. The GI type cooperative learning model influences collaboration skills and scientific literacy.